Resilience and mental state of lung recipients in the context of the COVID-19 pandemic - Izabela Jaworska; Robert Pudlo; Anna Mierzyńska; Tomasz Stącel; Maciej Urlik; Tomasz Hrapkowicz (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Lung transplantation is the only effective treatment method for patients with lung diseases in final stages. During treatment, the patient may experience numerous stressors that have an adverse effect on their mental state, which the COVID-19 pandemic may aggravate. The study aims to assess patients' resilience and mental state after lung transplantation in the context of the COVID-19 pandemic. Material and methods: A study using the General Health Questionnaire (GHQ-28), the Hospital Anxiety and Depression Scale (HADS), the Athens Insomnia Scale (AIS), and the Brief Resilience Coping Scale (BRCS) was conducted during the second wave of the COVID-19 pandemic on 40 patients in the distant period after lung transplantation, who had been tested with the General Health Questionnaire (GHQ-28) before the start of the pandemic. During the second wave of COVID-19, the patients were provided with constant, remote contact with the transplant center. Results: The average age of patients in the studied group was 51 ± 12 years. The majority were men (57.5%). The mental state of patients on the GHQ-28 scale did not deteriorate during the coronavirus pandemic. 70% of participants were characterized by a high level of coping resilience and 12.5% (5 patients) a low level. Psychological variables were not dependent on age. Their results did not differ significantly in terms of the type of transplant performed, gender, or being in a relationship. Conclusions: The second wave of COVID-19 did not negatively affect the mental state of lung recipients. The high percentage of sleep disorders in lung recipients requires attention and more profound research.